KEBERLANJUTAN PELAYANAN AIR BERSIH DI PERUMDA AIR MINUM TIRTA MEDAL KABUPATEN SUMEDANG - Akadun; Ahmad Hidayat; Dadi Kusnadi (LPPM UNSAP & FISIP UNSAP, 2020)
This study aims to determine the sustainability of clean water services and the factors that affect the sustainability of clean water services. This research is a descriptive type of research using a qualitative approach or often called the naturalistic method, because the assessment is carried out in natural conditions (Natural Setting). This research was conducted at the Regional Public Company Tirta Medal Drinking Water in Sumedang Regency in November 2020. The samples in this study were 12 people. Data collection is obtained from interviews, documentation and observation. After the data is obtained, it is analyzed using data reduction, data presentation and verification. The results showed (1) the factors that determine the sustainability of PERUMDA services regarding the availability of clean water raw materials, namely: the role of the Regional Government, the number of employees, the number of customers, clean water sources, and the availability of pipelines in PERUMDA so as to optimize the services provided to customers. (2) Actors or actors who determine the sustainability of clean water services at PERUMDA include the Regional Government, the Director, the Head of Division, and the District Office / Head. Then the employee who is one of the determinants is expected to be able to determine the sustainability of clean water services, and customers. (3) Sustainability of clean water services in Sumedang Utara Branch with 4096 subscribers. Plans to optimize the manufacture of deep wells to be implemented in the head office with a capacity according to geologists of 4-5 liters / second to optimize services in Sumedang Kota area. The sustainability of clean water services at the Cisitu branch consists of 2 work units, namely the Darmaraja service unit and the Cisitu branch. The Cisitu branch is supplied more than 20 liters / second and to meet the service needs of the Cisitu and Karangpakuan Units, it has been able to provide clean water services for 24 hours. The continuity of clean water services at Darmaraja Service Unit currently lacks clean water discharge. because the water discharge has started to decrease. In the long-term plan, there will be additional water debit through deep bore wells, so that consumers will not feel water shortages due to the rotating system, and can accept new customers. (4) Sustainability strategy PERUMDA has a strategy of adding new water sources, providing electricity networks to anticipate the dry season, and making mineral water products to explore potential income outside of new service connections. The program or policy of the Tirta Medal Regional Public Company for drinking water in the covid-19 pandemic situation provides relief to customers, namely in the form of eliminating fines.